Financing Specialized Property Development in Rural Southwestern Nigeria: A Source Analysis - Karuga, Ellen Waithira; Kithae, Peter P.; Kathula, Domeniter N. (Journal of Global Economy, Business and Finance, 2026)
The recent proliferation of sizeable buildings in the rural areas of Southwest of Nigeria where economic yardstick may not be the primary aim for such developments has continued to catch the attention of researchers. Specialized developments are so categorized because they are special by nature, size, design, land coverage, opulence and they are hardly sold in the open market. The properties are custom - built, and their types are rare: they should not have been found in the locations where they are sited in the first instance. Being so distinguished makes their appraisal to come with problems because the market data upon which to base their comparison with others are scarce and insufficient. This has made Valuers opt for advance methods such as Hedonic, Contingent and Artificial Intelligence Property Valuation Methods in their appraisals. This study centered at investigating the sources of financing such developments in the rural areas of the Southwestern part of Nigeria with the objective to determine if there are differences in the sources employed by property owners across the States in the region. Southwestern States are made up of six States sharing the same Yoruba language and of the same culture. Due to the spread of the region, Ondo, Osun and Ekiti States were sampled in the research. It was found out that owners of specialized developments in the region sourced their funding mainly from Commercial Banks, followed by Merchant Banks, Mortgage Institutions, and Insurance Companies in order of importance. The research also revealed that every development still has an element of personal contribution inform of equity contribution and that this runs throughout the lifetime of the development. A major problem that stares the owners in the face is the loan duration. Long term loans were found to account for 50% of the burrowed money, 33.3% are intermediate loans while 16.7% are short time; this however indicates that there is ample time at the disposal of owners to pay back burrowed funds.